STATODYNAMIC DISTURBANCES OF FUNCTIONS AS ONE OF THE REASONS FOR THE ACCUMULATED DISABILITY OF THE POPULATION IN THE ROSTOV REGION - I. G. Berezin; L. A. Yakimenko; F. V. Logvin; A. D. Nasytko (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
In the course of the study, it was possible to identify the weighted average values of the burden of static-dynamic diseases among the female and male population of young age. A continuous study was carried out in 2020 on the basis of the Main Bureau of Medical and Social Expertise in the Rostov Region. In the course of the work, a database was compiled on the accumulated disability in the Rostov region for people aged 18–45 years (23,248 cases). In the course of the study, five age-sex groups were identified: 1) 18–25 years old, 2) 26–30 years old, 3) 31–35 years old, 4) 36–40 years old, 5) 41–45 years old. The study of indicators of a separate age  group included the calculation of the frequency of accumulated disability,  assessment of the structure of the contingent, taking into account the causes and severity of disability. Statistical processing of the data obtained  was carried out by comparing the average values in the Statistica 10  application program. In the first studied age group, the incidence of accumulated disability is 87.9 cases per 10 thousand of the population, among them 17.7 cases per 10 thousand of the population are people with  disabilities. statodynamic disturbances (20.1%). In the second group, the  frequency of general disability is 70.9 cases per 10 thousand of the population, among them 17.0 cases per 10 thousand of the population are  people with disabilities with staticdynamic disorders (24.0%). In the third  group, the incidence of accumulated disability is 119.1 cases per 10 thousand of the population, among them 31.4 cases per 10 thousand of the population are disabled persons with static-dynamic disorders (26.4%). In the fourth group, the incidence of accumulated disability is 182.0 cases per  10 thousand of the population, among them 54.7 cases per 10 thousand of  the population are people with disabilities with static-dynamic disorders (30.0 %). In the fifth group, the frequency of general disability is 276.2 cases per 10 thousand of the population, among them 82.9 cases per 10 thousand  of the population are people with disabilities with static-dynamic disorders (30.0 %). Thus, the indicator of accumulated disability with statodynamic disorders is higher in the fifth age-sex group of the study (82.9  cases per 10 thousand population); in the structure of the severity of  disability, the third group prevails.